A iniciativa privada promove o lazer em São Paulo: o caso do parque Shanghai (1937-1968) - Gessi, Hennan [UNIFESP] (2017)
This Research Seeks To Highlight The Participation Of The Private Sector In The Process Of Dissemination Of Leisure Spaces In São Paulo Through The Analysis Of One Experience: The Parque Shanghai, A Private Enterprise Created In São Paulo During The 1930'S In The Context Of Its Expansion. The Research Will Examine, With Special Care, Textual And Iconographic Sources Trying To Understand The Way Which This Equipment Occupied In The City, At A Time When The Question Of Leisure Was Being Introduced, Dialoguing With The Achievements In Labor, The Expansion Of Demands For New Spaces And The Debates Around Regulation Of The Leisure Right.